The Effect of the Effectiveness Android-Based Prophet Muhammad’s Educational Media on Students’ Learning Results in Islamic Education - Ritonga, Maisaroh; Aditiya, Rahmad; Syawaluddin, Fauzi Ahmad (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2025)
This research intends to evaluate the impact of Android-based educational media on the learning achievements of sixth-grade students at SD Negeri 10 Rantau Utara in the Islamic Education subject. The approach employed is quantitative, utilizing a quasi-experimental design that incorporates pre-test and post-test assessments in the experimental group. The Validity and Reliability assessmet was conducted to evaluated the questionnaire’s validity, and the research data analysis was performed using a t-test for the hypothesis testing. The results from the study on data analysis methods indicate that among the 24 students, only 7 students (29.16%) achieved the KKM before utilizing the Android-based Prophet Muhammad (saw) educational media. Traditionally, it has not been achieved since the average score recorded is 66.66%, whereas the learning outcomes of students after the post test, students using Android-based Prophet (saw) educational media, reveal that among 24 students, 20 students (83.33%) have reached the KKM, and classically it has been achieved, with an average score of 83.12%, categorizing it as high. The effectiveness of using Android-based Prophet’s Education media is also recognized through the results of the t-test analysis. The study’s findings showed t Count = 7.06 and t table = 2.06, hence t Count > t Table or 7.06 > 2.06. Thus, it can be determined that H0 is rejected and Ha is accepted. This indicates that the efficiency of utilizing Android-based educational media about Prophet Muhammad (saw) positively impacts the learning achievements of sixth grade students at SD Negeri 10 Rantau Utara.